PENGARUH KOMUNIKASI TERAPEUTIK BIDAN TERHADAP KEPUASAN PASIEN BERSALIN DI RUMAH SAKIT BHAYANGKARA PUSDIK BRIMOB WATUKOSEK GEMPOL PASURUAN - M. Lukman Hakim; Kukuh Sinduwiatmo (Kanal: Jurnal Ilmu Komunikasi, 2013)
The objective of this study is to explain the effect of therapeutic communication done by midwives toward maternity patient satisfaction in Bhayangkara Pusdik Brimob hospital in Watukosek, Gempol Pasuruan. This study uses a correlational approach. Of the 1034 population of maternity patients in 2012, the researcher took Yamane formula so that the sample in this study were 91 respondents. The analysis uses simple linear regression formula. The conclusion of this study is that the results of 4,798 t and a significance value of 0.000. Values greater than 4,798 t 1,987 t table (df = 91-2 = 89; α = 0.05) and 0,000 T test significance value less than 0.05, then H0 is rejected and H1 is accepted, ie there is an effect of therapeutic communication by midwives toward satisfaction of maternity patient. While the results of the test R2 (R Square) obtained at 0.794 that patient satisfaction influenced by therapeutic communication is 79.4%, while 20.6% is influenced by other variables.